SEMIOTICS ANALYSIS OF BETAWI VERNACULAR ARCHITECTURE AT SETU BABAKAN, JAKARTA - Agustin Lakawa (International Journal on Livable Space, 2018)
AbstractIn traditional societies, it is not too difficult to integrate the style and symbols of a house because they have a common language of the same yet mutually understandable style. However, this can not be applied nowadays with the development of pluralistic cultures encountered by Betawi people. Semiotic enables community to reflect on various related issues in the form of architecture and spatial arrangement. This research was conducted to obtain information that will be used to complement semiotics analytical methods. Field data collection methods are done both visually through recording of buildings and orally through interviewing some of the residents. This research uses semiotics analysis model derived from Ferdinand de Saussure which was adapted by Charles Peirce and used by Charles Jencks. Semiotics discussion on the style of Betawi house at Setu Babakan area consists of four major parts: building orientation, zoning, building typology, and building ornament. The result of this study confirms that there are several changes on the four major parts to support the shift of the village into a cultural village. These changes represent the sign of adaptability of the community to support the preservation and maintenance of Betawi house in this cultural village. Keywords: style and symbol, vernacular architecture, Betawi traditional house